Exposure to dimethyl phthalate induces oxidative stress and autophagy in gill of Zebrafish via the PI3K/AKT/mTOR pathway: Protective role of 1,8-cineole - Zhihui Jiang; Yufei Du; Yilin Zhu; Jingyan Wu; Shengming Ma; Shaoting Weng; Kunpeng Zhang (Aquatic Toxicology, 2026)

Trichosanthes kirilowii Maxim. extract ameliorates ulcerative colitis in mice through modulation of metabolic homeostasis and restoration of gut microbiota balance - Shengming Ma; Qian Mao; Shaoting Weng; Zhihui Jiang; Chengwei Zhang; Xiao Liu; Jie Hao; Kunpeng Zhang (Natural Product Research, 2026)

Construction of a rAAV-SaCas9 system expressing eGFP and its application to improve muscle mass - Shaoting Weng; Yitian Zhao; Changhong Yu; Xiaofan Wang; Xuehan Xiao; Liqiang Han; Kunpeng Zhang; Jiang Wang; Guoyu Yang (Biotechnology Letters, 2021)
An ideal rAAV gene editing system not only effectively edits genes at specific site, but also prevents the spread of the virus from occurring off-target or carcinogenic risks. This is important for gene editing research at specific site in vivo. We report a single rAAV containing SaCas9 and guide RNAs under the control of subtle EF1a and tRNA promoters. The capacity of rAAV was compressed, and the editing efficiency was similar to that of the classical Cas9 system in vitro and in vivo. And we inserted the sequence of the green fluorescent protein eGFP into rAAV. The number of cells infected with the rAAV and the region in which the rAAV spreads were known by the fluorescent expression of eGFP in cells. In addition, we demonstrated that myostatin gene in the thigh muscles of C57BL/10 mice was knocked out by the rAAV9-SaCas9 system to make muscle mass increased obviously. The protein eGFP into rAAV has significant implications for our indirect analysis of the editing efficiency of SaCas9 in the genome of the target tissue and reduces the harm caused by off-target editing and prevents other tissue mutations. The rAAV system has substantial potential in improving muscle mass and preventing muscle atrophy.